2003
DOI: 10.1016/s0092-8674(03)00719-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Histone H1.2 in Apoptosis Induced by DNA Double-Strand Breaks

Abstract: It is poorly understood how apoptotic signals arising from DNA damage are transmitted to mitochondria, which release apoptogenic factors into the cytoplasm that activate downstream destruction programs. Here, we identify histone H1.2 as a cytochrome c-releasing factor that appears in the cytoplasm after exposure to X-ray irradiation. While all nuclear histone H1 forms are released into the cytoplasm in a p53-dependent manner after irradiation, only H1.2, but not other H1 forms, induced cytochrome c release fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
294
4
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(315 citation statements)
references
References 59 publications
11
294
4
6
Order By: Relevance
“…RNAs were converted to cDNAs using MMLV reverse transcriptase (Life Technologies) and oligo(dT) [12][13][14][15][16][17][18] (Amersham Biosciences). The cDNA was then amplified by polymerase chain reaction (PCR) using AmpliTaq Gold DNA polymerase (Applied Biosystems).…”
Section: Semiquantitative Rt-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…RNAs were converted to cDNAs using MMLV reverse transcriptase (Life Technologies) and oligo(dT) [12][13][14][15][16][17][18] (Amersham Biosciences). The cDNA was then amplified by polymerase chain reaction (PCR) using AmpliTaq Gold DNA polymerase (Applied Biosystems).…”
Section: Semiquantitative Rt-pcr Analysismentioning
confidence: 99%
“…1 Recent studies have revealed two potential mediators of p53-dependent apoptosis, p53 upregulated modulator of apoptosis (PUMA) 11 and Histone H1 (especially Histone H1.2). 12 Once transactivated by p53, they cause the release of mitochondrial proapoptotic molecules into the cytosol and initiate the caspase cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, GFP-labeled H1.1, H1.2, and H1.3 were mainly found in euchromatin, whereas H1.4 and H1.5 were more common in heterochromatin (12). Some of the H1 subtypes have been assigned specific roles such as H1.2, which participates in apoptosis signaling after induction of DNA double strand breaks (15).…”
mentioning
confidence: 99%
“…This subtype of histone H1 is the one which binds most weakly to DNA [23] and is also released from nuclei of apoptotic cells upon genotoxic damage [24]. Nuclei of HeLa cells expressing PA-GFP-H1.2 were either irradiated at 1050 nm to induce DNA-SBs in a rectangular volume, or left unirradiated.…”
Section: Resultsmentioning
confidence: 99%